Postwar Youth Violence: A Mirror of the Relationship between Youth and Adult Society - Sabine Kurtenbach (German Institute of Global and Area Studies (GIGA), 2012)
Postwar societies are high-risk contexts for youth violence. Nevertheless, not all postwar societies are equally violent. This article explores how these variations can be explained by focusing on the interaction between youths and adult society in a comparison of Guatemala and Cambodia. Starting from the concept of socialization and the possibilities of performing status passages to adulthood, it analyzes not only the different risk factors but also the agency of young people and society in trying to cope with and overcome obstacles on the pathway to adulthood. Different patterns of war termination and of reconstruction after war's end are identified as major intervening variables that explain the variations in youth violence in as well as across the case studies.
Keywords: 300; violence; youth; status passages; Guatemala; Cambodia; Jugendkriminalität; Sozialisation; Jugendliche; Guatemala; Kambodscha